Morden tactic in diagnosis and treatment of early colon cancer (review of literature) - A. N. Sidorova; V. N. Klimenko; A. M. Sherbakov; O. B. Tkachenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
According to the literature review, the use of modern endoscopes with high resolution and a narrow-band imagine function with optical magnification, as well as autofluorescence, chromoscopy, endosonography, makes it possible to establish a diagnosis of early colorectal cancer with a high degree of accuracy. Nowadays, endoscopic submucosal dissection and endoscopic mucosal resection are the methods of choice in the treatment of early (Tis, T1sm1N0M0) colon cancer.